The Effectiveness of Using Selfie Photos on Improving Students’ Ability to Express the Fact: a Case of The Seventh Grade Students of SMP Negeri 1 Kragan Rembang - Nur Azizah (ETERNAL (English Teaching Journal), 2016)
The objectives of the study are: 1) To find out the ability to express the fact of the students taught using selfie photos. 2) To find out the ability to express the fact of the students taught without selfie photos. 3) To find out the significant differences of the ability to express the fact between the students taught using selfie photos and those taught without selfie photos. The study uses descriptive quantitative research. The population of this research is the seventh grade students of SMP Negeri 1 Kragan Rembang. The writer takes VII I as experimental group that consists of 36 students and VII D as control group that consists of 36 students as sample. The writer found that the mean score for experimental group in pre-test is 71.44, and after this class is given a treatment by using selfie photos, the result of post-test is 81.33. The mean score for control group in pre-test is 70.22, and the post-test score is 73.89. The writer uses t-test formula to know the significant difference of the ability to express the fact between the students taught using selfie photos and those taught without using selfie photos. The t-test score is 3.455 for 5 percent (0.05) alpha level of significance. The percentage of t-table 5% is 1.99. The calculation shows that t-test is higher than t-table (3.455>1.99). It shows that there is significant difference of the ability to express the fact of the seventh grade studentsat SMP Negeri 1 Kragan Rembang those taught using selfie photos and those taught without using selfie photos. It can be concluded that selfie photos as a media in improving the ability to express the fact of the students is effective. Selfie Photos makes the students active and enjoy in learning English in the classroom. So, the writer suggests to all of the teacher in general to apply selfie photos media in teaching learning process, especially in learning English.